Numerical simulation on mixed convection in a porous medium heated by a vertical cylinder - Li, Ling (Strojniški vestnik, 2005)
Numerical simulation has been performed for mixed convection of heated vertical cylinder with a constant temperature in a saturated porous medium subjected to lateral flow. Four different geometric aspect ratios 5, 10, 25 and 50 were considered, which give ratios of axial length to diameter. Based on dimensional analysis and nonlinear regression, correlations for the Nusseltnumber against the Rayleigh and the Peclet numbers have been obtained.
Keywords: prenos toplote; tok fluida; mediji porozni; simuliranje numerično; cilindri; numerične metode; simulacije